Reproductive Phenology and Floral Anatomy of Aloe vera - A.H. Rathod; S.K. Parmar (Contemporary Research and Perspectives in Biological Science Vol. 9, 2025)
In the present study on the reproductive phenology and floral anatomy of Aloe vera, it was observed that flowering occurred from the last week of November to the second week of December. The plant produced tubular flowers arranged on a brightly colored cylindrical raceme. The flowers were bisexual, possessing both male and female reproductive organs. The perianth comprised six lobes, with sepals and petals combined. Each flower contained six stamens, and the ovary was superior, with the sepals, petals, and stamens inserted below the ovary. Anthesis within the raceme was completed within 5 to 10 days. Flower opening began at 7:00 AM and continued until 3:00 PM, with the peak period of dehiscence observed between 10:00 AM and 12:00 PM. Stigma receptivity was highest during anthesis. The fruits of Aloe vera reached full maturity within 60 to 67 days.